Early Childhood Educational Settings and School Absenteeism for Children With Disabilities - Arya Ansari; Michael A. Gottfried (SAGE Publishing, 2018)
Data from the Early Childhood Longitudinal Study Kindergarten Class of 2010-2011 were used to examine the implications of preschool and full-day kindergarten enrollment for the subsequent school absences of 2,056 children with disabilities. Results suggest that children with disabilities who went to preschool were absent less frequently in kindergarten, but these benefits did not persist through the end of first grade. Conversely, children with disabilities who attended full-day kindergarten programs were absent more frequently during the kindergarten year as compared with children in part-day programs, but these children experienced a sharper drop in absenteeism throughout the following school year resulting in no differences in school absences in first grade. No multiplicative benefits emerged for attending both preschool and full-day kindergarten. And even though these aforementioned benefits of preschool diminished rapidly, there were lingering academic benefits through the end of first grade because of improvements in earlier school attendance.